Advertising Costs and Equilibrium: A Reply - Smith, Henry (Review of Economic Studies, 1947)
Journal Article Advertising Costs and Equilibrium: A Reply Get access Henry Smith Henry Smith Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 15, Issue 1, 1947, Pages 40–41, https://doi.org/10.2307/2295927 Published: 01 April 1947